Echocardiographic navigation in transapical neochord mitral valve repair with significant mitral regurgitation - N. S. Titov; V. V. Komok; A. S. Nemkov; G. G. Khubulava (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Significant mitral regurgitation is currently a widespread acquired valvular heart disease and is associated with a significant decrease in survival and deterioration in quality of life. One of the new, unclearly studied, minimally invasive method for correcting significant mitral regurgitation is transapical neochord mitral valve repair, where echocardiography is the key imaging tool.The OBJECTIVE was to analyze the data of world studies devoted to the problem of echocardiographic navigation in transapical neochord mitral valve repair, to determine the echocardiographic criteria applicable to neochord implantation surgery. METHODS AND MATHERIALS. The analysis of studies about using echocardiography in the transapical neochord mitral valve repair has been carried out. Databases searched in this review included PubMed, ResearchGate, and Hindawi.RESULTS. During the analysis, we figured out that 2D and 3D transesophageal echocardiography is the main method for mitral valve imaging during transapical neochord mitral valve repair. Specific parameters which can be useful in addition for standard echocardiographic protocol of mitral valve evaluation have been identified.CONCLUSION. The results of the analysis showed that it is necessary to summarize the experience of present studies and standardize the approach to echocardiographic evaluation of the mitral valve during transapical neochord mitral valve repair.